Evaluation of suya (tsire) – an intermediate moisture meat product in Ogun State, Nigeria (2013)
A study was conducted to evaluate suya (tsire) an intermediate moisture meat product in Ogun State. Sixty suya sticks were used. Twelve suya sticks were prepared in the laboratory while 12 suya sticks were collected from each zone of the state namely: Yewa, Egba, Remo and Ijebu. They were analyzed for physical, chemical, microbiological and organoleptic characteristics. The results showed that there were significant (P < 0.05) differences in physical properties of suya samples analyzed with suya from Yewa zone having the highest (P < 0.05) water holding capacity and suya prepared in the laboratory and those from Egba zone had the highest (P < 0.05) shear force, while the pH was least (P < 0.05) in suya prepared from laboratory. Moisture content was least (P < 0.05) in suya samples prepared in the laboratory and from Egba zone, while ash content was higher (P < 0.05) in suya from Yewa, Remo and Ijebu Zones. Aerobic bacteria and coliform counts were least (P < 0.05) in suya prepared in the laboratory and from Egba Zone, while lactic acid bacteria were higher (P < 0.05) in suya prepared in the laboratory and from Egba Zone. The results revealed that suya samples prepared in the laboratory were accepted more (P < 0.05) followed by those from Egba and Remo Zones. However, microbial loads observed on Suya (tsire) samples in this study were not as high as those reported by previous workers. Nonetheless, efforts should be made to educate meat and meat products (Suya) processors in Ogun State on the importance of hygiene and proper packaging and preservation to avoid contamination and spoilage of meat products during processing and sale.